ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN BERAS MEDIUM DI PASAR TRADISONAL BATURAJA TIMUR KABUPATEN OGAN KOMERING ULU - Eviani, Cheniya; Lastinawati, Endang; Ogari, Putri Ayu (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
This study aims to analyze the factors that influence the demand for medium rice in the East Baturaja Traditional Market, Ogan Komering Ulu District. The implementation of this research was carried out from December to February 2023. The research method was carried out using a  survey method. The method of determining the sample used is incidental sampling. The sample used is 60 consumers consisting of 30 new market samples and 30 upper market samples. The analytical method used is multiple linear regression. The results showed that the factors that significant influence the demand for medium rice in the East Baturaja Traditional Market, Ogan Komering Ulu District ware medium rice prices, substituted rice prices, opinions, and number of family members. While educations has no significant effect on the demand for medium rice in the East Baturaja Traditional Market, Ogan Komering Ulu District.